Effect of iodine prophylaxis during pregnancy on neurocognitive development of children during the first two years of life. - Velasco, Inés; Carreira-Soler, Mónica; Piedad, Santiago; Muela, José Antonio; García-Fuentes, Eduardo; Sánchez-Muñoz, Baltasar; Garriga, María J.; González-Fernández, María C.; Rodríguez, Álvaro; Caballero, Francisco F.; Machado, Alberto; González-Molero, Stella; et al. (My University, 2009)
Context: The association between thyroid function during pregnancy and the later mental and psychomotor development of the child is supported by numerous experimental, clinical and epidemiological studies. Objective: To evaluate the psychological development of infants aged 3 to 18 months whose mothers had received 300 μg of potassium iodine during the first trimester of their pregnancy. Design and Study Subjects: The study included 133 women who had received 300 μg of potassium iodine and 61 women who had received no iodine supplements. Main Outcome Measures: The neuropsychological status of the children was evaluated with the Bayley Scales of Infant Development and measurements were made of TSH, FT3, FT4 and urinary iodine. Results: Those children whose mothers had received an iodine supplement of 300 μg had a more favorable psychometric assessment than those of the other group of mothers. They had higher scores on the Psychomotor Development Index (p=0.02) and the Behavior Rating Scale. Conclusions: Dietary iodine supplements not only have no harmful effect on the neurodevelopment of the children, they may even be beneficial. Given the possible presence of confounding variables not controlled for in this study, these findings should be considered as preliminary.
Dr. Carreira, please find attached the published version of your article requested below. Sincerely Tim Beardsley
Keywords: Desarrollo cognitivo; Neurociencia cognitiva; Iodine Prophylaxis; Neurocognitive Development; Pregnancy; Children